Implementing education system reform: Local adaptation in school reform of teaching and learning. (January 2021) - Dimmock, Clive; Tan, Cheng Yong; Nguyen, Dong; Tran, Tu Anh; Dinh, Thang Truong
Highlights: Within-school enablers were influenced by external enablers in re-shaping teaching and learning. Internal enablers took a path of professional development changing school culture, both of these then impacted leadership. School-level enablers of change enable them to adapt to national reforms even in a centralized communist system. Conceptualizing the change process in schools involves critical mass, inertial momentum, lock-in and emergent new pathways. The explanatory power of complex adaptive system theory – complemented by tight-loose coupling theory – was confirmed. Abstract: This paper has two purposes: first, to investigate centre- periphery, and within-school relationships and processes by which Vietnam schools undertake system reform implementation; second, to develop the explanatory power and complementarity of two theories – complex adaptive system theory and loose-tight coupling. Main findings - schools' internal enablers driving reforms were shaped by external enablers; a plethora of internal enablers then worked in concert to implement the intended reforms (eg. the take-up of student-centred teaching and learning); in the local adaptation process, school culture and professional development were pre-eminent. Conclusions – complex adaptive system theory was validated in how Vietnam schools locally adapted policy.